2013
DOI: 10.4236/ajps.2013.48a004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations and Selections for High Isoflavone Black Soybean Mutants Induced by NaN<sub>3</sub> Treatment

Abstract: Sodium azide (NaN 3 ) (2 mM) was used to induce mutation in black soybean variety CRWD for improvement of isoflavone content. The individual selections were made in M6, M7 and M8 generations, respectively. Both high levels of isoflavones and medium seed size traits were used as selection criteria. Across three growth seasons, the selected five NaN 3 -induced mutants accumulated more total isoflavones (average increases of 5% to 25%) than their wild type variety CRWD. Four mutants yielded more (average increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a study where the isoflavone synthase gene was transformed to promote higher isoflavone concentrations, the total isoflavone concentration in the callus tissues of the transformed line was three- to sixfold higher than that in the control cell line [ 57 ]. In another study, NaN 3 -induced soybean mutants had higher total isoflavone concentrations (on average 5% to 25% higher) than their wild-type cultivar [ 58 ]. Furthermore, many studies have demonstrated that postharvest UV-C treatment in detached leaves, vegetables and fruits increases the secondary metabolite contents and their biosynthetic enzymes [ 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study where the isoflavone synthase gene was transformed to promote higher isoflavone concentrations, the total isoflavone concentration in the callus tissues of the transformed line was three- to sixfold higher than that in the control cell line [ 57 ]. In another study, NaN 3 -induced soybean mutants had higher total isoflavone concentrations (on average 5% to 25% higher) than their wild-type cultivar [ 58 ]. Furthermore, many studies have demonstrated that postharvest UV-C treatment in detached leaves, vegetables and fruits increases the secondary metabolite contents and their biosynthetic enzymes [ 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical mutagenesis using sodium azide (NaN3) in soybean induced genotypic variations that can influence the isoflavone content (Jeng et al. ). Here, we used gamma ray as a mutagen, and the selected mutant lines showed variation in their anthocyanin and isoflavone contents.…”
Section: Discussionmentioning
confidence: 99%
“…The content of isoflavones and anthocyanins in soybean seeds can vary according to the genotype (Kim et al 2005, Ha et al 2009). Chemical mutagenesis using sodium azide (NaN3) in soybean induced genotypic variations that can influence the isoflavone content (Jeng et al 2013). Here, we used gamma ray as a mutagen, and the selected mutant lines showed variation in their anthocyanin and isoflavone contents.…”
Section: Discussionmentioning
confidence: 99%